The Influence of Investment Knowledge, Investment Motivation, Minimum Capital, Financial Literacy, Investment Risk, and Investment Return on Stock Investment Interest among University Students in Purwokerto - Lyra Arecha; Nirmala Nirmaa; Dian Safitri P. Koesoemasari (Darul Yasin Al Sys, 2026)
University students’ interest in stock investment remains varied despite the increasing accessibility of capital market participation through technological advancement and investment facilities. This condition indicates a gap between expanding investment opportunities and students’ readiness to engage in rational investment behaviour. This study aims to analyze the influence of investment knowledge, investment motivation, minimum capital, financial literacy, investment risk, and investment return on stock investment interest among university students in Purwokerto. A quantitative approach with a descriptive-explanatory design was employed, involving students from the Faculty of Economics and Business at Wijayakusuma University, Purwokerto, from the 2022–2024 cohorts. A total of 93 respondents were selected using proportionate stratified random sampling. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression, supported by classical assumption tests, the F-test, t-test, and coefficient of determination analysis. The findings reveal that investment knowledge, investment motivation, minimum capital, financial literacy, investment risk, and investment return positively and significantly influence students’ stock investment interest. Investment knowledge emerged as the most dominant variable, while the model explained 62.20% of the variation in investment interest. The study concludes that students’ stock investment interest is shaped by cognitive, psychological, financial, and evaluative factors. This study contributes to financial behaviour and capital market education literature by demonstrating the multidimensional determinants of student investment interest. The practical implications emphasize the need to strengthen investment education, financial literacy, and affordable investment access to encourage informed and sustainable student participation in stock investment activities.